Penilaian Kadar Fenol Dalam Urine Pada Pekerja Dengan Metode Quantitatif Risk Assement (QRA) - Suharni A. Fachrin; Alfina Baharuddin; Saskia Anrah Maharani; Zarina Nur Halidah (Window of Public Health Journal, 2026)
According to the Agency for Toxic Substances and Disease Registry (ATSDR), benzene is an organic solvent that is carcinogenic. Benzene can enter the body through the respiratory tract, digestion, and skin contact. The study found no association between work duration and phenol levels (p-value = 0.205), which reassures policymakers that factors beyond exposure time influence benzene absorption. The development of a Quantitative Risk Assessment (QRA) model aims to identify workplace chemical exposure cases, helping protect workers' health by linking environmental exposure to health risks and predicting benzene concentrations in workers' urine. This study aims to assess phenol levels in workers' urine using the QRA method. The research design is an analytical observational study with a cross-sectional approach. The study was conducted on motorcycle repair shop workers in Makassar City. The sampling technique used was purposive sampling. Data collection was carried out through surveys using questionnaires, observations, interviews, and laboratory examinations. The results of the study showed that there was no relationship between work period and phenol levels in the urine of workshop workers (p-value = 0.281), nor between exposure duration and phenol levels in the urine of workshop workers (p-value = 0.205). However, there was a relationship between the use of personal protective equipment (PPE) and phenol levels in the urine of workshop workers (p-value = 0.000). Therefore, motorcycle workshop workers are expected to comply with the use of PPE while working to minimize the risk of benzene exposure.